Structural Equation Modeling of Bulimia Nervosa Disorder Based on Emotional Flexibility and Self Esteem: The Mediating Role of Fear of Negative Evaluation - Peighamy, Raana; Hosseini Nasab, Davood; Alivandi Vafa, Marziyeh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to examine a structural model of Bulimia Nervosa based on emotional flexibility and self esteem, with fear of negative evaluation hypothesized as a mediating variable. Methods and Materials: This descriptive–correlational, cross sectional study employed structural equation modeling. Participants were individuals exhibiting symptoms of Bulimia Nervosa, recruited through purposive sampling in Iran in 2025. Data were collected using the Gormally Binge Eating Scale, the Emotional Flexibility Questionnaire, the Fear of Negative Evaluation Scale, and the Rosenberg Self Esteem Scale. Data analysis was conducted using SPSS version 27 and SmartPLS version 4, with a significance level set at 0.05. Findings: Emotional communication was not significantly associated with Bulimia Nervosa symptoms (β = 0.126, t = 1.884, p = 0.060). In contrast, negative emotion regulation (β = −0.173, t = 1.970, p = 0.049) and positive emotion regulation (β = −0.238, t = 2.596, p = 0.009) demonstrated significant negative associations with Bulimia Nervosa symptoms. Positive emotion regulation was also negatively related to fear of negative evaluation (β = −0.169, t = 2.061, p = 0.039), as was self esteem (β = −0.807, t = 4.893, p < 0.001). However, none of the indirect pathways through fear of negative evaluation reached statistical significance. Conclusion: The findings indicate that emotional flexibility—particularly positive and negative emotion regulation—and self esteem exert direct effects on Bulimia Nervosa symptoms, whereas fear of negative evaluation does not function as a mediating mechanism within the tested model. These results suggest that psychological interventions for Bulimia Nervosa may be more effective when primarily focused on enhancing emotion regulation capacities and strengthening self esteem rather than targeting evaluative social fears.